Simulation and Experimental Analysis of Heat Treatment for Steel Tie Rods: A Review - Kunal Kumar Singh; Girish M. Dhote; Chetan Mahatme; Prashant Kamble (International Journal of Mechanical Dynamics and Systems Analysis, 2025)
The study is related to the actual heat treatment and simulation of the physical deformation of the steel tie rod and compares the observations for process optimization. The general methodology is to go for either traditional or induction hardening after getting the chemical composition of the material, followed by tempering, which is a key technique for improving the mechanical properties of materials, strength, hardness, etc., and to release stresses. This technology is widely used in the fields of manufacturing, aerospace, and robotics. This study is done in the current manufacturing scenario, which faces many rejections due to physical deformation leading to loss of money and time, so simulation aids in heat treatment are done before the actual process is done in a furnace for reducing rejection. Introducing computer-aided engineering (CAE) with the process of heat treatment is quite challenging and complex; hence, optimizing processes of heat treatment, a finite element analysis software for heat treatment, like COMSOL and Analysis System (ANSYS), is used for simulation. The boundary conditions and parameters in conventional gas carburizing heat treatment are studied and will be used in simulation software for analysis purposes. This will help the manufacturer to analyze the process to select appropriate heat treatment process parameters and hardness as per the application to avoid wastage. Moreover, integrating experimental data with simulation enhances the accuracy of predictive models and enables real-time adjustments. This approach not only improves product quality but also contributes to sustainable manufacturing by reducing energy consumption, minimizing rework, and extending component life.
Keywords: Deformation; Heat treatment simulation; gas carburizing; hardening; heat treatment furnace